Prevalence and factors associated with inappropriate anti- diabetic medication therapy among type 2 diabetes mellitus patients at the medical and surgical wards of Mbarara Regional Referral Hospital, Uganda - Nigussie, Konjit Abebe; Shegena, Efrata Ashuro; Stephen, Obwoya Paul; Namugambe, Juliet Sanyu; Yadesa, Tadele Mekuriya (Plos one, 2022)
Background: Inappropriate Anti-Diabetic Medication Therapy (IADT) refers to a drug-related problem and includes ‘ineffective drug therapy’, ‘unnecessary drug therapy’, ‘dosage too high’, and ‘dosage too low’. This study aimed to determine the prevalence and factors associated with IADT among T2DM patients at Mbarara Regional Referral Hospital, Uganda (MRRH). Method: A prospective cross-sectional study was conducted at the medical and surgical wards of MRRH from November 2021 to January 2022. One hundred and thirty-eight adult patients aged 18 years and above, with T2DM, were recruited using consecutive sampling. Patient file reviews and interviewer-administered questionnaire was used for data collection. The data were entered into and analyzed using SPSS version 25. Descriptive analysis was employed to describe the population and determine the prevalence of IADT. Types of IADTs were identified using Cipolle’s DRP classification tool. A univariate and multivariate logistic regression analysis was used to identify factors significantly associated with IADT. The Pvalue of<0.05 was considered statistically significant at 95% confidence interval. Results: A total of 138 hospitalized T2DM patients were studied. Eighty (58.0%) were females, and 70 (50.7%) were>60 years of age. Out of a total of 138 participants, 97 experienced at least one IADT, with an estimated prevalence of 70.3%. ‘Dosage too high’ (29.2%) and ‘dosage too low’ (27.9%) were the most common type of IADTs. Age>60 years (AOR, 8.44; 95% CI, 2.09–10.90; P-value = 0.003), T2DM duration of<1 year (AOR, 0.37; 95% CI, 0.11–0.35; P-value = 0.019), and HbA1c of<7% (AOR, 9.97; 95% CI, 2.34–13.57; P-value = 0.002) were found to be factors significantly associated with the occurrence of IADTs. Conclusion: The overall prevalence of inappropriate anti-diabetic medication therapy among T2DM patients admitted to medical and surgical wards of MRRH was 70.3%. The most common type of IADT in this study was ‘dosage too high’, accounting for almost one-third followed by ‘dosage too low’ accounting for a quarter of total IADTs. Age greater or equal to 60 years, T2DM duration of<1 year, and HbA1c of<7% during the current admission were found to be factors significantly associated with the occurrence of IADTs in hospitalized T2DM patients.
Keywords: Anti-diabetic Medication Therapy; Type 2 diabetes mellitus patients; Surgical wards; Uganda